1995
DOI: 10.1002/cne.903520408
|View full text |Cite
|
Sign up to set email alerts
|

Expression of chondroitin sulfate and keratan sulfate proteoglycans in the path of growing retinal axons in the developing chick

Abstract: Previous investigations have identified proteoglycans in the central nervous system during development and have implicated some proteoglycans as axon guidance molecules that act by inhibiting axon extension. The present study investigated the pattern of immunoreactivity for several glycosaminoglycans common to certain proteoglycans relative to growing retinal axons in the developing chick visual system and in retinal explant cultures. Immunostaining for chondroitin-6-sulfate, chondroitin-4-sulfate, and keratan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0

Year Published

1997
1997
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(36 citation statements)
references
References 53 publications
3
33
0
Order By: Relevance
“…Graded expression of attractants or repellents inside the retina is thus likely to be part of the mechanism that underlies the centrally directed retinal axon projection. Although our result is consistent with the previous findings that staining of CS-56 antibody persists in the center of the retina in chicken (McAdams and McLoon, 1995;Ring et al, 1995), we cannot rule out that a particular constituent of the CSPGs may still be involved in intraretinal axon targeting or subjected to the regulation by Zic3. The identities of the core proteins of the CSPGs have remained undefined.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Graded expression of attractants or repellents inside the retina is thus likely to be part of the mechanism that underlies the centrally directed retinal axon projection. Although our result is consistent with the previous findings that staining of CS-56 antibody persists in the center of the retina in chicken (McAdams and McLoon, 1995;Ring et al, 1995), we cannot rule out that a particular constituent of the CSPGs may still be involved in intraretinal axon targeting or subjected to the regulation by Zic3. The identities of the core proteins of the CSPGs have remained undefined.…”
Section: Discussionsupporting
confidence: 83%
“…10A,B). Similar to previous reports (McAdams and McLoon, 1995;Ring et al, 1995), we also observed that the staining of an anti-chondroitin sulfate proteoglycans (CSPGs) antibody (CS-56) persists in the center of the retina in chicken, albeit at a much lower level than in the periphery. This suggests that CSPGs may colocalize with the growing optic axons and play a different role in retinal axon guidance.…”
Section: Misexpression Of Zic3 May Activate the Expression Of A Curresupporting
confidence: 90%
See 1 more Smart Citation
“…These displaced or disorganized axons ultimately exit the optic disc. D, Dorsal; V, ventral. located in regions in which RGCs extend actively (McAdams and McLoon, 1995;Ring et al, 1995). Together, this suggests that fundamentally distinct mechanisms may regulate intraretinal axon guidance in the mammalian and chick retina.…”
Section: Slits Regulate Distinct Aspects Of Intraretinal Guidance In mentioning
confidence: 93%
“…For example, CSPGs are present in boundary and guidance regions during development and are usually growth inhibitory (Asher et al, 2000b). KSPGs are also present in boundary and guidance structures in development (Snow et al, 1990b;Geisert et al, 1992;Geisert and Bidanset, 1993;Gonzalez et al, 1993;McAdams and McLoon, 1995) although these have variable e¡ects upon neurite growth in vitro (Snow et al, 1990a;. In contrast, developmental studies (Halfter, 1993) and cell culture experiments (Wang and Denburg, 1992;Faissner et al, 1994;Walz et al, 1997) indicate that HSPGs are often growth-permissive molecules.…”
mentioning
confidence: 99%